Study of BIM Tools Implementation among Contractors During Project Construction Phase in Construction Industry - Rosli, Firdaus; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
Building Information Modelling (BIM) provides significant benefits to the contractors. However, BIM tools in construction phase projects seem not fully been implemented and rarely used by contractors. This is because of the certain problem faced by contractors, which are interoperability, high implementation cost, lack of knowledge by site workers about BIM tools technologies, and other consultants not using BIM tools. Therefore, the purpose of this research to study what is the current practices, challenges and benefits of BIM tools implementation among contractors at the construction phase. The literature review was carried out to discover BIM tools implementation among contractors during the construction phase. Qualitative research methodology conducted by interviews with the contractors which currently involved and have been involved in projects using BIM tools for residential and commercial projects in Malaysia. All data obtained from the interviews were analyzed and carried out by using content analysis. Therefore, both data from the literature review and the interviews were used to complete this research. The contractor realizes the importance of using BIM tools during the construction phase such as Revit and Navisworks that assist them in the construction site. The awareness of the importance of using BIM tools and cost becomes a major challenge for the contractors to implement BIM tools during the construction phase. This research needs to know how BIM tools can be fully implemented during construction, to help the contractor achieve several advantages provided in the construction phase by the implementation of BIM tools.